Exploring The Strategic Role of Knowledge Transfer in Fostering Continuous Innovation and Competitive Advantage in Indonesia Creative Industry 4.0 - Dian Alanudin (Syntax Idea)
In Indonesia's Creative Industry 4.0, effective knowledge transfer is crucial for fostering continuous innovation. Despite the country's cultural richness, the transfer of knowledge within the creative sector remains suboptimal, hindering growth and innovation. Tacit knowledge predominantly resides within individuals, limiting dissemination within organizations and resulting in the loss of heritage and creative assets. However, amidst these challenges, significant opportunities exist, Indonesia's creative industry, with notable unicorns and a large workforce, has the potential for economic growth and development. Yet, the transition to Industry 4.0 demands enhanced knowledge transfer capabilities. While Industry 4.0 presents opportunities for Indonesia to compete globally, effective knowledge transfer remains limited. This study aims to address this gap by investigating the nature and consequences of knowledge transfer within Indonesia's creative industry, with a focus on fostering continuous innovation. By prioritizing knowledge transfer and leveraging ICT and HRM resources, firms can enhance their competitive advantage and performance in the dynamic landscape of Industry 4.0. Through this research, insights are provided to facilitate sustained growth and innovation in Indonesia's creative industry